Long-term nitrogen fertilization alters the partitioning of amino acids between citrus leaves and fruits - Zhao, Yuanlai; Xiong, Huaye; Luo, Yayin; Hu, Bin; Wang, Jie; Tang, Xiaodong; Wang, Yuehong; Shi, Xiaojun; Zhang, Yueqiang; Rennenberg, Heinz (Frontiers in Plant Science, 2025)
IntroductionThe growth of evergreen fruit trees is influenced by the interaction of soil nitrogen (N) and leaf amino acid contents. However, information on free amino acid contents in leaves of fruiting and non-fruiting branches during long-term N fertilizer application remains scarce.MethodsHere, a four-year field experiment (2018-2021) in a citrus orchard revealed consistently lower total N and amino acid contents in leaves of fruiting compared to non-fruiting branches.Results and discussionAppropriate N fertilizer application increased free amino acid and total N contents in leaves of both types of branches and fruits, but excessive amounts led to decreases. Correlation analysis showed that, in the early stage of fruit development, leaves on both types of branches can meet the N requirements of the fruit (R²=0.77 for fruiting, R²=0.82 for non-fruiting). As fruits entered the swelling stage, a significant positive correlation emerged between fruiting branch leaves and fruit total N content (R²=0.68), while the R² for leaves on non-fruiting branches dropped to 0.47, indicating a shift in N supply towards leaves on fruiting branches. Proline and arginine are the most abundant amino acids in these leaves. At fruit maturity, these amino acids account for more than half of the total amino acids in the fruit (29.0% for proline and 22.2% for arginine), highlighting their crucial role in fruit development. Further research is needed to investigate amino acid transport and distribution mechanisms between citrus leaves and fruits.